Odpowiedzi

2009-12-08T20:06:23+01:00
A)2x+2-3x-6=7x-1
2x-3x-7x=-1+6-2
-8x=3
x=-3/8
b)4x+2(x+5)-7=3-(2x+3)
4x+2x+10-7=3-2x-3
6x-2x=7-10
4x=-3
x=-3/4
Najlepsza Odpowiedź!
2009-12-08T20:07:23+01:00
2x+2-3x-6=7x-1
-x-4=7x-1 /+4
-x=7x+3 /-7x
-8x=3 /:(-8)
x=-trzy ósme

4x+2(x+5)-7=3-(2x+3)
4x+2x+10-7=3-2x-3
6x+3=-2x /+2x
8x+3=0 /-3
8x=-3 /:8
x=-trzy ósme

Pozdrawiam :)
2009-12-08T20:13:03+01:00
A) 2x+2-3x-6=7x-1
2x-3x-7x=-2-1+6
8x=3 /:8
x=trzy ósme

b) 4x+2(x+5)-7=3-(2x+3)
4x+2x+10-7=3-2x-3
6x+3=-2x
6x+2x=3
8x=3 /:8
x=trzy ósme